Pathological validation and significance of micrometastasis in sentinel nodes in primary breast cancer - Rampaul, R.S.; Miremadi, A.; Pinder, S.E.; Lee, A.; Ellis, I.O. (BioMed Central Ltd, 2001)
In embracing a multidisciplinary approach to the management of patients with sentinel node biopsy in breast cancer, the pathologist task is to screen sentinel nodes for possible metastasis. The consequences of missing sentinel node micrometastasis can directly influence treatment strategies, and this screening therefore has to be performed with more attention than usual. There is presently great diversity in the histopathological work-up of sentinel nodes, with many centres employing additional techniques such as immunohistochemistry, reverse transcription polymerase chain reaction or flow cytometry in addition to routine haematoxylin and eosin staining. In this review, we address the pathological validation and significance of micrometastasis in sentinel node biopsy in primary breast cancer